MONOMORMATIVITY VS HETERONORMATIVITY: IMPLICATIONS FOR THE PERCEPTION OF PARTNERS IN A RELATIONSHIP - Rodrigues, D. L.; Aybar Camposano, G.; Lopes, D.; Aleksandra Huic (International Conference on LGBT+ Psychology and Related Fields, 2022)
People stigmatize others that deviate from normative behaviors in relationships. However, recent evidence showed that romantic partners in consensual nonmonogamous (CNM) relationships are dehumanized, when compared to their monogamous counterparts. Interestingly, this dehumanization occurred regardless of whether partners were heterosexual or in a same-sex male relationship. We aimed to further understand these findings by examining how people perceive relationship dynamics, morality and values underlying these relationships. We conducted an experimental study with 181 heterosexual Portuguese adults (151 women; Mage = 28.90, SD = 10.11) and asked participants to read the description of two people in a relationship using a 3 Relationship agreement (monogamous vs. open relationship vs. polyamorous) x 2 Sexual orientation of the partners (same-sex male vs heterosexual) between-subjects design. After reading the description, participants were asked to make a series of judgments about both partners: likelihood of engaging in unsafe sex behaviors, morality and values. Results showed differences according to relationship agreement. Specifically, CNM (vs. monogamous) partners were perceived as less moral (honest, sincere and confident), as having higher incidences of sexual transmitted infections, and as using condoms more frequently. These partners were also attributed more individual values (e.g., hedonism, stimulation) and less traditional ones. There were also differences according to the sexual orientation of the partners. Same-sex male (vs. heterosexual) partners were attributed more values overall (e.g., achievement, universalism. No interaction between both factors emerged in either dependent measure. Overall, this study extended findings from the dehumanization literature and showed that stigmatization based on deviations from mononormativity overcome the stigmatization based on deviations from heteronormativity.